Cultivation of Sapodilla Harvest ‘Zapota Chips’ Through Participatory Action Research Approach in Sampung Village, Rembang District - Febriyanti, Fitri; Rizki Nuansa Fitri, Dara; Silfiana Restuningrum, Laila; Zainurrofiqoh, Alfita; Machya, Izzatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The COVID-19 pandemic significantly impacted the economy of rural communities in Indonesia, including Sampung Village, Sarang District, Rembang Regency. This research aims to enhance the economic value and shelf life of the sapodilla harvest by transforming it into Zapota Chips. Using a Participatory Action Research (PAR) approach, the study involved community members in the process. Key strategies included trial production of sapodilla products, branding and packaging of Zapota Chips, launching the product, establishing the UMKM Guyub Berkarya organizational structure, and conducting seminars with the Dinas DAGKOPUKM Rembang Regency. Additionally, marketing relationships were cultivated, and mentoring was provided for UMKM members. Financial planning discussions and coordination for distribution were also conducted. The initiative engaged local resources, particularly young women and housewives, to enhance economic empowerment. The results indicate that these efforts successfully increased the economic value of the sapodilla harvest, fostering local development. This program exemplifies how community involvement and strategic planning can harness local potential for broader economic benefits.